2012
DOI: 10.1007/978-3-642-35063-4_64
|View full text |Cite
|
Sign up to set email alerts
|

Classification-Based Prediction on the Retweet Actions over Microblog Dataset

Abstract: Abstract. We present the ideas and methodologies that we used to address the WISE Challenge 2012 on predicting the retweet actions over microblog dataset. We employ classification and simulation mechanisms as our main technique, in which the original event dataset is classified into specific categories and then the similar curves are simulated to complete the task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…When we set the error threshold to about 20%, the proposed model achieved a significantly outstanding precision at about 0.5, in contrast to conventional models, which showed a precision of around 0.3 and 0.2, respectively. In [7], despite excluding 4,790 unpredictable datasets from all 8,944 test datasets, it shows the lowest performance among them. We concluded that the user-preference property is changeable as time passes and is not handled flexibly when new users are detected.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…When we set the error threshold to about 20%, the proposed model achieved a significantly outstanding precision at about 0.5, in contrast to conventional models, which showed a precision of around 0.3 and 0.2, respectively. In [7], despite excluding 4,790 unpredictable datasets from all 8,944 test datasets, it shows the lowest performance among them. We concluded that the user-preference property is changeable as time passes and is not handled flexibly when new users are detected.…”
Section: Resultsmentioning
confidence: 98%
“…The precision in predicting the number of retweets was evaluated according to the respective error threshold. Because using only 33 test data in the previous models [4] and [7] caused low reliability, we evaluated the test data shown in Table 3 to enhance the reliability. Figure 12 shows the results of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations